2001
DOI: 10.1103/physrevlett.87.097003
|View full text |Cite
|
Sign up to set email alerts
|

Optical Conductivity and Penetration Depth inMgB2

Abstract: The complex conductivity of a MgB2 film has been investigated in the frequency range 4 cm −1 < ν < 30 cm −1 and for temperatures 2.7 K < T < 300 K. The overall temperature dependence of both components of the complex conductivity is reminiscent of BCS-type behavior, although a detailed analysis reveals a number of discrepancies. No characteristic feature of the isotropic BCS gap temperature evolution is observed in the conductivity spectra in the superconducting state. A peak in the temperature dependence of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 14 publications
4
50
0
Order By: Relevance
“…A conduction electron spin resonance study in the frequency range from 9 GHz to 225 GHz also reported an excess signal below T c [26]. A similar observation was made from an optical study on MgB 2 thin films with energies ranging from 0.5 meV to 3.7 meV [39] where the complex conductivity,…”
Section: Introductionmentioning
confidence: 51%
“…A conduction electron spin resonance study in the frequency range from 9 GHz to 225 GHz also reported an excess signal below T c [26]. A similar observation was made from an optical study on MgB 2 thin films with energies ranging from 0.5 meV to 3.7 meV [39] where the complex conductivity,…”
Section: Introductionmentioning
confidence: 51%
“…On the other hand, we note that there are at least six low-T experiments showing or at least suggesting power-law behaviors which seem to indicate gap nodes (Panagopoulos et al 2001, Zhukov et al 2001, Pronin et al 2001, Ohishi et al 2003. [Admittedly, the lowest temperatures in some of these experiments are too high to be convincing.…”
mentioning
confidence: 76%
“…69 From experience with YBCO, however, it seems that it is necessary to reach temperatures well below 0.05T c to differentiate between different symmetries by methods of microwave response. 70 Other data, derived from muon spin rotation 71 and optical conductivity, 72 yield the penetration-depth ϰT 2 while an ac susceptibility experiment fits the penetrationdepth data with a temperature dependence T 2.7 . 73 These works are clearly inconsistent with the exponential falloff expected for a s-wave gap, Eq.…”
Section: Relation Of Our Findings To Existing Literaturementioning
confidence: 99%